2002
DOI: 10.1002/ajh.10053
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of children with Langerhans cell histiocytosis with 2‐chlorodeoxyadenosine

Abstract: Langerhans cell histiocytosis (LCH) is a disorder characterized by proliferation of activated Langerhans cells. Immune dysregulation is believed to be part of the pathogenesis. Although current therapies are very effective at inducing remission, multiple recurrences and long-term sequelae are common for patients with low-risk disease, and a signi®cant proportion of young patients die of their disease. More effective therapies based on the pathogenesis of LCH are needed. We investigated the use of 2-chloro-deox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…These results further confirm and extend the observations made in other studies of 2-CDA in children with LCH. [9][10][11] 2-CDA is a purine analog resistant to the catalyzation by enzyme ADA. The metabolite inhibits the DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results further confirm and extend the observations made in other studies of 2-CDA in children with LCH. [9][10][11] 2-CDA is a purine analog resistant to the catalyzation by enzyme ADA. The metabolite inhibits the DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…This strong rationale led to the usage of 2-CDA in histiocytic disorders. Many small studies [9][10][11][12]16,17] have been conducted which are summarized in Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown the efficacy of 2CdA when used against LCH. [14][15][16] Because histiocytes are derived from monocytes, we are hopeful that histiocytic sarcoma may show a favorable response to 2CdA. Although there are no published studies suggesting the efficacy of 2CdA in histiocytic sarcoma, we are aware of an adult patient with this entity who remained free of the disease for 6 months after 5 cycles of 2CdA.…”
Section: Tablementioning
confidence: 99%